Dynamic deformation of the femoral head occurs on weightbearing in Legg- Calves- Perthes disease: A traslational pilot study. (July 2020) - Aarvold, A.; Lohre, R.; Chhina, H.; Mulpuri, K.; Cooper, A.
No abstract available